Analysis of nickel export restriction and downstream policy in Indonesia - Putra, Agung Tri; Samputra, Palupi Lindiasari (International Journal Labs, 2023)
With 21 million metric tons of nickel deposits, or ? of global reserves, Indonesia possesses an abundance of the metal. The purpose of this study is to evaluate the export and processing policies of the Indonesian government regarding nickel and how they relate to global nickel requirements in light of future energy estimates. This study's methodology, which gathers information from official websites, government papers, mass media, and literature, is based on qualitative assumption analysis. The findings indicate that a revision is necessary to ESDM Ministerial Regulation Number 11 of 2019. This policy has a negative effect since the government failed to consider a number of factors while drafting it, including the effects on the environment, the disparity in benefits between China and Indonesia, and the distribution of social implications. Since this policy fosters future national economic progress, it can be deemed appropriate. Impacts on social, environmental, and national resilience still need to be taken into account. The study's findings indicate that, although expert assumptions and a number of other factors on social and environmental issues vary, the government's assumptions, which give priority to the economic sector, do not. The notion of nickel's added value is currently the sole issue that the government views as a major concern, despite the fact that downstream nickel applications can have a good societal impact.